Molecular epidemiology of human enterovirus 71 strains and recent outbreaks in the Asia-Pacific region: Comparative analysis of the VP1 and VP4 genes - Cardosa, M.J (Centers for Disease Control and Prevention (CDC), 2020)
10.3201/eid0904.020395